SQVDT: A scalable quantitative vulnerability detection technique for source code security assessment. (2nd October 2020) - Akram, Junaid; Luo, Ping
Summary: Vulnerability detection and exploit is becoming a very important part of security, especially in malware code delivery, hacking a system, efforts to create patches, improving the source code, or updating a software. Vulnerabilities in applications, including browsers, media players, online services, document readers, and so forth. are often exploited and cause a serious damage. In this article, we propose a vulnerability detection technique to detect vulnerabilities in software, as well as shared libraries at source code level. We crawl the vulnerable source code by tracing and locating the patch files from different web sources according to their CVE‐numbers and built a fingerprint index of 2931 vulnerable files. Then we developed a vulnerability detection approach based on code clone detection technique and detect hundreds of vulnerabilities in thousands of GitHub open source projects, which are not noticed before as vulnerable. We detected vulnerabilities in some very famous recently available software, including latest version of Linux, HTC‐kernel, FindX‐8.1‐kernel, and in 7‐TB of C/C++ source code (152, 823 open source projects). In this study, we discuss some of the very high severity level (CVSS) vulnerabilities that are detected by our approach. Furthermore, we performed an empirical evaluation and verification on these vulnerabilities, including intraproject clone vulnerabilities, copied‐kernel clone vulnerabilities, and library‐used clone vulnerabilities. Our technique is very fast, efficient, reliable, practical, scalable, and can be implemented at industrial level. The comparison with the state‐of‐the‐art tools shows the effectiveness of our approach.